Compression of biomedical images and signals - Naït-Ali, Amine; Cavaro-Ménard, Christine (Digital signal and image processing series., 2008)
During the last decade, image and signal compression for storage and transmission purpose has seen a great expansion. But what about medical data compression? Should a medical image or a physiological signal be processed and compressed like any other data? The progress made in imaging systems, storing systems and telemedicine makes compression in this field particularly interesting. However, this compression has to be adapted to the specificities of biomedical data which contain diagnosis information.As such, this book offers an overview of compression techniques applied to medical data, i.